2016
DOI: 10.1021/acsnano.6b07071
|View full text |Cite
|
Sign up to set email alerts
|

Hydration Effects Turn a Highly Stretched Polymer from an Entropic into an Energetic Spring

Abstract: Polyethylene glycol (PEG) is a structurally simple and nontoxic water-soluble polymer that is widely used in medical and pharmaceutical applications as molecular linker and spacer. In such applications, PEG's elastic response against conformational deformations is key to its function. According to text-book knowledge, a polymer reacts to the stretching of its end-to-end separation by a decrease in entropy that is due to the reduction of available conformations, which is why polymers are commonly called entropi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
114
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(123 citation statements)
references
References 72 publications
9
114
0
Order By: Relevance
“…Both PEG and HA form higher-order structures due to hydrogen bonding between neighboring monomers and/or between monomers and water. 9,14,23 High forces have been shown to disrupt these interactions, 9,14,24 which leads to deviations from WLC behavior, and can lead to elasticitybased estimates of l p that are smaller than l p in the absence of force. This issue is minimized here: those prior observations are based on AFM studies at a force scale of ≈100 pN.…”
Section: Results and Comparison To Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Both PEG and HA form higher-order structures due to hydrogen bonding between neighboring monomers and/or between monomers and water. 9,14,23 High forces have been shown to disrupt these interactions, 9,14,24 which leads to deviations from WLC behavior, and can lead to elasticitybased estimates of l p that are smaller than l p in the absence of force. This issue is minimized here: those prior observations are based on AFM studies at a force scale of ≈100 pN.…”
Section: Results and Comparison To Datamentioning
confidence: 99%
“…Further, in the low-force regime, absolute extension becomes very small, leading to sensitivity to systematic errors based on, e.g., the precise tethering position of the polymer to the probe. 8,9 An alternate approach is based on the analysis of the fluctuations in polymer extension. 3,7 The fluctuation-based method is an application of linear response theory 10 and is discussed in detail elsewhere.…”
Section: Fluctuation Estimates Of Polymer Elasticitymentioning
confidence: 99%
“…[12] The force-extension curvesw ere well fitted by the worm-like chain (WLC) with ap ersistence length of about 0.4 nm and ac ontour length of approximately 40 nm ( Figure S7, Supporting Information), consistent with our calculation andp revious works on the PEG linker. [13] The observed single rupture peak (in contrast to multiple unfolding peaks) in the force-extension curvess uggest that HFBI remained folded before detaching from the surfaces. The high stability of HFBI due to the disulfide bridges supports this conclusion.…”
mentioning
confidence: 95%
“…Hence the OEG‐ spacer has to bridge a distance of approximately 2 nm. The length distribution of flexible OEG chains that we obtained from our previous MD simulations, suggested that the OEG‐linker must consist of at least 6–14 ethylene glycol units to span the distance between the ligand core and the binding sites (c.f. Supporting Information)…”
Section: Resultsmentioning
confidence: 99%